Hubungan antara Self-Compassion dengan School Well-Being Pada Siswa SMA - Alma Dwi Afina; Eem Munawaroh (Jurnal Bimbingan dan Konseling Indonesia, 2022)
The purpose of this study was to determine the relationship between self-compassion and school well-being in high school students in the District of Grabag. The type of research used is quantitative research with ex post facto research design. The data collection tools used are the Self-Compassion Scale and the School Well-Being Scale. The sampling technique used a proportional stratified random sampling technique. Then the hypothesis testing is using Spearman rank correlation analysis. The self-compassion scale consists of 23 items and has a reliability value of 0.810. Furthermore, the School Well-Being Scale consists of 31 items with a reliability value of 0.776. Self-compassion for high school students in Grabag District is in the moderate category (M = 66.53; SD = 7.90) and school well-being for high school students in Grabag District is in the medium category (M = 83.79; SD = 7.68). The results of the Spearman rank correlation test showed that R = 0.497, R2 = 0.235, p <0.05, which indicates that self-compassion has a relationship with school well-being in high school students in Grabag District. Self-compassion has a contribution of 23.5%. Abstrak: Tujuan penelitian ini untuk mengetahui hubungan antara self-compassion dengan school well-being pada siswa SMA di Kecamatan Grabag. Jenis penelitian yang digunakan adalah penelitian kuantitatif dengan desain penelitian ex post facto. Alat pengumpulan data yang digunakan adalah Skala Self-Compassion dan Skala School Well-Being. Teknik sampel menggunakan teknik proportional stratified random sampling. Kemudian pengujian hipotesis yaitu menggunakan analisis korelasi spearman rank. Skala Self-Compassion berjumlah 23 item memiliki nilai reliabilitas 0,810. Selanjutnya Skala School Well-Being berjumlah 31 item memiliki nilai reliabilitas 0,776. Self-compassion pada siswa SMA di Kecamatan Grabag berada pada kategori sedang (M = 66,53 ; SD = 7,90) dan school well-being pada siswa SMA di Kecamatan Grabag berada pada kategori sedang (M = 83,79 ; SD = 7,68). Pada hasil uji korelasi spearman rank diperoleh hasil yaitu R = 0,497, R2 = 0,235, p < 0,05, yang menunjukkan bahwa self-compassion terdapat hubungan dengan school well-being pada siswa SMA di Kecamatan Grabag. Self-compassion memiliki kontribusi sebesar 23,5%.